SWOT Analysis for Electric Vehicles (EVs) in Thailand - Kongklaew, C; Phoungthong, K; Techato, K (International Journal of Integrated Engineering, 2021)
Nowadays, transport activities are one of the major contributors to greenhouse gas (GHG) emission. It also causes air pollutants in major cities around the world as particulate matter (PM), carbon monoxide (CO) and carbon dioxide (CO2). Thai government has implemented numerous policies in reducing GHG emission of which Electric Vehicles are an interesting option. Electric vehicles (EVs) are interesting as a result of new technology they deploy, which can reduce GHG emission and friendly to the environment. This study, therefore aims to investigate EVs factors and their important by using SWOT analysis. We analyzed the strength, weaknesses, opportunities and threats related to EVs adoption in Thailand. We also established strategies for EVs adoption, via competition and attractive investment to entice local and international investors, gather and share information on countries that adopted EVs, encourage communities in discussion about EVs technology, smart grid designation, deploying well trained technicians, as well as EVs supporting policies and promotion. The result showed that policies on EVs in Thailand are concentrated on providing support to only manufacturers, entrepreneurs and importing car companies. While, the consumers supportâ€™ policies are given lesser importance. These ï¬ndings are important for the relevant authorities in Thailand in developing appropriate EVs policy for sustainable transportation.